2006
DOI: 10.1016/j.bmc.2006.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of a classical 2,4-diamino-5-substituted-furo[2,3-d]pyrimidine and a 2-amino-4-oxo-6-substituted-pyrrolo[2,3-d]pyrimidine as antifolates

Abstract: Two classical antifolates, a 2,4-diamino-5-substituted furo [2,3-d]pyrimidine and a 2-amino-4-oxo-6-substituted pyrrolo [2,3-d]pyrimidine, were synthesized as potential inhibitors of dihydrofolate reductase (DHFR) and thymidylate synthase (TS). The syntheses were accomplished by condensation of 2,6-diamino-3(H)-4-oxo-pyrimidine with α-chloro-ketone 21 to afford two key intermediates 23 and 24, followed by hydrolysis, coupling with L-glutamate diethyl ester and saponification of the diethyl ester to afford the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…As shown in Fig. 4, two reduction peaks for (2) were obtained at about − 0.6 V and − 0.8 V. Increasing of peak height at −0.6 V with addition of Sb(III) solution to the medium indicated that this peak can be assigned to reduction of Sb(III) to Sb(0). Chronoamperometric measurements also show that transferred electron number in this electrochemical reduction was 3.…”
Section: Synthesis and Formulation Of The Compoundsmentioning
confidence: 90%
See 4 more Smart Citations
“…As shown in Fig. 4, two reduction peaks for (2) were obtained at about − 0.6 V and − 0.8 V. Increasing of peak height at −0.6 V with addition of Sb(III) solution to the medium indicated that this peak can be assigned to reduction of Sb(III) to Sb(0). Chronoamperometric measurements also show that transferred electron number in this electrochemical reduction was 3.…”
Section: Synthesis and Formulation Of The Compoundsmentioning
confidence: 90%
“…Chronoamperometric measurements also show that transferred electron number in this electrochemical reduction was 3. The other peak showing no change is adsorption peak of the (2).…”
Section: Synthesis and Formulation Of The Compoundsmentioning
confidence: 92%
See 3 more Smart Citations